Is Corruption Good or Bad for FDI? Empirical Evidence from Asia, Africa and Latin America - Jalil, Abdul; Qureshi, Amina; Feridun, Mete (Savez Ekonomista Vojvodine, 2016)
This article revisits the relationship between corruption and Foreign Direct Investment inflows in a panel of 42 countries from 1984 to 2012 using pooled mean group estimator in a dynamic heterogeneous panel setting using Westerlund and ARDL panel cointegration tests where the estimations are carried out by three different estimators: the pooled mean group (PMG), mean group (MG), and the dynamic fixed effect (DFE) estimators in order to examine both the long- and short-term effects of corruption on FDI inflows. The results suggest that corruption has a positive impact on FDI inflows in the case of Asia and Africa; and a negative impact in the case of Latin America.
Keywords: FDI; Corruption; Panel data